Turbidity currents can dictate organic carbon fluxes across river-fed fjords: an example from Bute Inlet (BC, Canada) - Hage, S; Galy, VV; Cartigny, MJB; Heerema, C; Heijnen, MS; Acikalin, S; Clare, MA; Giesbrecht, I; Gröcke, DR; Hendry, A; Hilton, RG; Hubbard, SM; et al. (American Geophysical Union, 2022)
The delivery and burial of terrestrial particulate organic carbon (OC) in marine sediments is important to quantify, because this OC is a food resource for benthic communities, and if buried it may lower the concentrations of atmospheric CO2 over geologic timescales. Analysis of sediment cores has previously shown that fjords are hotspots for OC burial. Fjords can contain complex networks of submarine channels formed by seafloor sediment flows, called turbidity currents. However, the burial efficiency and distribution of OC by turbidity currents in river-fed fjords had not been investigated previously. Here, we determine OC distribution and burial efficiency across a turbidity current system within Bute Inlet, a fjord in western Canada. We show that 62% ± 10% of the OC supplied by the two river sources is buried across the fjord surficial (30–200 cm) sediment. The sandy subenvironments (channel and lobe) contain 63% ± 14% of the annual terrestrial OC burial in the fjord. In contrast, the muddy subenvironments (overbank and distal basin) contain the remaining 37% ± 14%. OC in the channel, lobe, and overbank exclusively comprises terrestrial OC sourced from rivers. When normalized by the fjord’s surface area, at least 3 times more terrestrial OC is buried in Bute Inlet, compared to the muddy parts of other fjords previously studied. Although the long-term (>100 years) preservation of this OC is still to be fully understood, turbidity currents in fjords appear to be efficient at storing OC supplied by rivers in their near-surface deposits.